تأثير نمط اتخاذ القرار القيادي لتجنب الازمات على مستوي أداء الموارد البشرية في المنشآت الرياضية - بورنان, مصطفى; نعمي, عبدالقادر; شيبوط, إبراهيم (جامعة الوادي - University of Eloued, 2020)
إن تحليل السلوك الإنساني في المنظمة أو المنشآت الرياضية وتفسير طبيعته وإدراك حاجاته الضرورية من خلال مستوى الأداء الوظيفي المعبر عنه في ظل الظروف والأوضاع التنظيمية السائدة، يمكن الوقوف على مواطن الضعف و القصور التي تحتاج إلى تحسين و تطوير مما يحقق فعالية تنظيمية للمنظمة و توفير مناخ تنظيمي ملائم، حتى يستطيع الأفراد أداء و تنفيذ الأدوار المطلوبة منهم و تقديم الخدمات للمستفيدين منها وسط أجواء مريحة و مشجعة. وهدفت هذه الدراسة إلى معرفة تأثير نمط اتخاذ القرار على مستوى أداء الموارد البشرية في مركب محمد بوضياف بالجزائر العاصمة ، ، كما شملت عينة الدراسة المسحية 30 بين مدراء ورؤساء مصالح ، وقد تم استخدام المنهج الوصفي لملائمته لطبيعة البحث المراد القيام به ، وتمت معالجة البيانات إحصائيا باستخدام معامل الارتباط سوبرمان ،وك2، مع استخدام الجداول المركبة لمعرفة التأثير بين نمط اتخاذ القرار و الأداء ، وقد اسفرت النتائج إلى عدم تجاوب أفراد العينة، وأن نمط اتخاذ القرار لا يؤثر على أداء الموارد البشرية في مركب محمد بوضياف حسب عينة الدراسة ، ولهذا تم وجوب وضع اقتراحات تحث على ضرورة الاهتمام نمط اتخاذ القرار من أجل تحسين مستوى أداء الموارد البشرية . Abstract: The analysis of human behavior in the organization or sports facilities, the interpretation of its nature and the realization of its necessary needs through the level of functional performance expressed in the prevailing organizational conditions and conditions, it is possible to identify weaknesses and deficiencies that need improvement and development in order to achieve organizational effectiveness of the organization and provide an organizational climate Convenient, so that individuals can perform and implement the roles required of them and provide services to their beneficiaries in a comfortable and encouraging atmosphere. This study aimed to find out the effect of the decision-making pattern on the level of human resource performance in the Mohamed Boudiaf complex in Algiers, and the survey sample included 30 managers and heads of departments. The descriptive approach was used to suit the nature of the research to be done, and the data were processed statistically using Superman correlation coefficient, and K2, with the use of composite tables to know the effect between the pattern of decision-making and performance, and the results resulted in non-response of the sample members, and that the decision-making pattern does not affect the performance of human resources in the Mohamed Boudiaf compound according to the study sample. The necessity of developing proposals urging the need to pay attention to the pattern of decisionmaking in order to improve the level of human resources performance
مقال
Keywords: الإدارة ; القرار القيادي ; المنشآت الرياضية ; الموارد البشرية ; الأزمات; management, leadership decision, sports facilities, human resources, crise